PERANAN KEPALA DISTRIK DALAM MEWUJUDKAN GOOD GOVERNANCE DI DISTRIK SALKMA KABUPATEN SORONG SELATAN - BLESIA, URIA; RUMAPEA, PATAR; TAMPONGANGOY, DEYSI (JURNAL ADMINISTRASI PUBLIK, 2018)
The weakness of the implementation of community services that become the scope of duties andfunctions that can be used by the government / district in an effort to improve the valuable performance forthe community. The role of the district head in coordinating community empowerment activities has notbeen well implemented, this can be proven by many problems that arise in the villages / villages of Masihvery minimal ability of the community in managing the efforts through community empowerment activitiesprogrammed by the government and to So far there has been no direct socialization of the Districtgovernment in providing information on how to manage and improve business through communityempowerment. The goal is to realize Good Governance (good governance) in serving the community asexpected. Methods ie Open Obsevation And Interviews Of 13 Informants: . district , . Sekertaris, . PeopleCommunity, Personnel, People. So the analysis is descriptive qualitative approach. It is his conclusionsthat provide the best service to the community and benefit and mobilize the community to engage ingovernance and development. Suggestions that are capable of applying the Good Governance Principles orgood government indicators, provide good assistance, advice and input in assisting, merging the serviceprocess to the community. Transparency / openness in information that is free, adequate, understandableand monitored by all parties and accessible to all interested parties. Accountability / responsibility byinterested parties in providing satisfactory service to Salkma District of South Sorong District. in an effortto improve district performance, and the process of motivating, mobilizing communities to engage ingovernance and development.Keyword : Rule, Of Head Distric, Making Good Governance.